Potential Utilization of Kaolin from South Kalimantan as a Substitute for Import Clay in Cement Board Making - Faiza Elisa Hasfianti; I Gede Dewa Putra Prabawa; Nurhidayati Nurhidayati; Rinnie Nintasari; Nurmilatina Nurmilatina (Jurnal Keramik dan Gelas Indonesia, 2021)
The   cement   board   industry   in   Indonesia   still depends   on   imported   materials,   such   as   the cement  board  industry  in South Kalimantan which  still uses clay  raw materials  from  Taiwan.  Limited  information  on  the potential use of local clay as an important clay substitution is the reason this research is needed. Identification of local clay factors was carried out by XRD, XRF, and SEM testing. The kaolin that was  tested was the kaolin Tatakan and Limamar. The   results  of  the  analysis   of  the  kaolin  material  were compared  with  the imported clay. The analysis  showed that the   clay   used   by   the  industry   was   illite  with  the  main compound  content  of  SiO2  (54.63%)  and  Al2O3  (28.23%). The results of the analysis of local clay (kaolin) tests showed that the content of compounds with imported clay was shown by kaolin placemat (SiO2  55.92%, Al2O3 29.13%), kaolin Limamar (SiO2  55.04%, Al2O3 32.71%). The quality of the application of kaolin as  a substitute for imported clay in the manufacture of cement board on a laboratory scale shows the result  that  is  not much different in the density  and porosity values.  The  strength  value  of  cement  board  with  kaolin limitation  gives  a  high  enough  value  but  it  is  below  the standard value for PT SNI's cement board product.